Need analysis for digital instructional materials of the Translation Theory Course in Indonesia - Rudy Sofyan; Bahagia Tarigan; Rohani Ganie (Universitas Syiah Kuala, 2023)
The essential role of translation in intercultural communication leads to the inclusion of translation as one of the courses in universities worldwide, including Universitas Sumatera Utara (USU), Indonesia. However, little research has been conducted on the development of instructional translation materials. This study aimed to determine the need for digital instructional materials for the Translation Theory course administered in USU’s English Literature Study Program. The need analysis in this research was conducted using a survey method. The participants were the seventh-semester students who had taken the courses on translation, the translation lecturers, and the professional translators. The data were collected using questionnaires and interviews. These instruments were developed based on the document analysis of the previous instructional materials used by the lecturers in teaching the Translation Theory course. The data were analyzed and interpreted using a 4-Point Likert Scale. The results indicated that the instructional materials for a Translation Theory course need to include clear objectives and approaches, topics guiding them to translation theory mastery, and exercises that cover both translation theory and practice. In addition, the results indicate that the participants need the material resources and exercises in a digital form. Although this study was conducted in the context of USU, the findings may be applied as the basis for developing translation courses in other universities in Indonesia, and other countries that treat English as a Foreign Language in their education systems.